2008
DOI: 10.4049/jimmunol.181.3.1978
|View full text |Cite
|
Sign up to set email alerts
|

Amyloid Precursor-Like Protein 2 Increases the Endocytosis, Instability, and Turnover of the H2-Kd MHC Class I Molecule

Abstract: The defense against the invasion of viruses and tumors relies on the presentation of viral and tumor-derived peptides to CTL by cell surface MHC class I molecules. Previously, we showed that the ubiquitously expressed protein amyloid precursor-like protein 2 (APLP2) associates with the folded form of the MHC class I molecule Kd. In the current study, APLP2 was found to associate with folded Kd molecules following their endocytosis and to increase the amount of endocytosed Kd. In addition, increased expression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
46
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 32 publications
(51 citation statements)
references
References 59 publications
4
46
1
Order By: Relevance
“…Although our previous studies demonstrated that APLP2 is bound to the endocytosed K d molecule, the specific location where the binding occurs was not identified (4). In the present study, we established that APLP2 binds K d at the cell surface before these two proteins internalize into the same endocytic vesicles.…”
contrasting
confidence: 45%
See 3 more Smart Citations
“…Although our previous studies demonstrated that APLP2 is bound to the endocytosed K d molecule, the specific location where the binding occurs was not identified (4). In the present study, we established that APLP2 binds K d at the cell surface before these two proteins internalize into the same endocytic vesicles.…”
contrasting
confidence: 45%
“…Internalized Together-Previous studies from our laboratories showed that APLP2 co-localized in endosomes with K d internalized from the cell surface and that APLP2 could be co-immunoprecipitated with internalized K d (4). To determine whether the interaction between APLP2 and K d occurs at the cell surface, K d molecules at the surface of HeLa-etK d cells were labeled with the 34-1-2 Ab on ice for 20 min, and then the cells were lysed and Ab complexes isolated with Protein A-Sepharose.…”
Section: Aplp2 and K D Bind At The Plasma Membrane And Arementioning
confidence: 87%
See 2 more Smart Citations
“…Although their critical importance for the interaction of E3/19K with HLA-I alleles not present in 293 cells cannot be excluded their conservation may imply an essential role for the interaction with other potential E3/19K target proteins. Interestingly, E3/19K was shown to increase complex formation of certain MHC-I alleles with the amyloid precursor-like protein 2, which has been implicated in peptide transfer (37,69) and in modulation of the stability and endocytosis of some murine and human MHC-I alleles (70,71).…”
Section: Discussionmentioning
confidence: 99%